Mechanisms of activation of the classical pathway of complement by Hageman factor fragment. - Ghebrehiwet, B (1983)
The mechanism by which a fragment of activated Hageman factor (HFf) activates the classical pathway of complement in serum or platelet-poor plasma has been further delineated. When serum or platelet-poor plasma was incubated with various concentrations of HFf, the total complement hemolytic activity was reduced in a dose-dependent manner. This activation appears to be due to the direct interaction of HFf with macromolecular C1, since incubation of purified C1 with HFf resulted in dissociation of the subunits with concomitant reduction of C1r antigenicity that is indicative of C1 activation. HFf-dependent activation was prevented by prior treatment of HFf with the active site-directed inhibitor, H-D-proline-phenylalanine-arginine chloromethyl ketone or with a specific inhibitor of activated HF derived from corn. Incubation of HFf with highly purified C1r also resulted in activation of C1r as assessed directly using a synthetic substrate or indirectly by activation of C1s and consumption of C2. However, incubation of HFf with highly purified C1s resulted in formation of activated C1s (C1s-) but this was less efficient than HFf activation of C1r. We therefore conclude that activation of C1 in macromolecular C1 is the result of HFf conversion of C1r to C1r; activation of C1s then occurs primarily by C-1r and to a lesser degree by the direct action of HFf.